Organization And Recruitment Of Human Resources Management And Its Impact On The Promotion And Development Of Sports Practice - Koriche , Ali; boukherass, Ramdane (sports creativity, 2025)
The abstract : The abstract : The research tackled the contribution of the purposes of organizing and , recruitment as basic to manage the Human Resources for the promotion and development of the sport practice in the Algerian civil protection sector. The researcher considers these purposes raise the level of the latter , which is reflected in the improvement of the performance of employees to serve the public better. In which he highlighted the duties mentioned above and proposed future solutions to better management of human resources in a scientific manner and from which to produce important results that would promote and develop the level of sports practice.